Catalase compromises the development of the insect and mammalian stages of Trypanosoma brucei - Horáková, Eva; Faktorová, Drahomíra; Kraeva, Natalia; Kaur, Binnypreet; Van Den Abbeele, Jan; Yurchenko, Vyacheslav; Lukeš, Julius (The FEBS journal, 2020)
Catalase is a widespread heme-containing enzyme, which converts hydrogen peroxide (H2 O2 ) to water and molecular oxygen, thereby protecting cells from the toxic effects of H2 O2 . Trypanosoma brucei is an aerobic protist, which conspicuously lacks this potent enzyme, present in virtually all organisms exposed to oxidative stress. To uncover the reasons for its absence in T. brucei, we overexpressed different catalases in procyclic and bloodstream stages of the parasite. The heterologous enzymes originated from the related insect-confined trypanosomatid Crithidia fasciculata and the human. While the trypanosomatid enzyme (cCAT) operates at low temperatures, its human homolog (hCAT) is adapted to the warm-blooded environment. Despite the presence of peroxisomal targeting signal in hCAT, both human and C. fasciculata catalases localized to the cytosol of T. brucei. Even though cCAT was efficiently expressed in both life cycle stages, the enzyme was active in the procyclic stage, increasing cell's resistance to the H2 O2 stress, yet its activity was suppressed in the cultured bloodstream stage. Surprisingly, following the expression of hCAT, the ability to establish the T. brucei infection in the tsetse fly midgut was compromised. In the mouse model, hCAT attenuated parasitemia and, consequently, increased the host's survival. Hence, we suggest that the activity of catalase in T. brucei is beneficial in vitro, yet it becomes detrimental for parasite's proliferation in both invertebrate and vertebrate hosts, leading to an inability to carry this, otherwise omnipresent, enzyme.
Keywords: trypanosoma; Animals; hydrogen peroxide; Hydrogen Peroxide; katalasa; catalase; development; Trypanosoma; peroxid vodíku; Trypanosoma brucei brucei; zvířata; hmyz; Catalase; Insecta